The Effect Of Capital Structure, Earning Management, Profitability, Free Cash Flow And Environment Cost On Firm Value With Dividend Policy As Moderating Variables In Pharmaceutical Sub Sector Companies Listed On The 2007-2019 Indonesia Stock Exchange Peri - Remilia Aprilia Ginting (Jurnal Sains Sosio Humaniora, 2021)
Firm value is one of the branchmark of the success in firm management in its operation so that its customers will trust it. The objective of the research was to analyze the influence of capital structure, earnings management, profitability, free cash flow and environment cost on firm value in pharmacyl companies that carry out Initial Public Offering (IPO) policies for the period 2007-2019. It also tested the variable of dividend policy as moderating variable in this research model.The Population are companies that carry out an Initial Public Offering (IPO) policy for the period 2007-2019. The population of this study was 104, the sample selection method of this study used the purpoive sampling method with a total of 8 companies that met the criteria. The type of data used is secondary data and the data analysis technique used is cross sectional data analysis technique with the help of Eviews 10 software. The results of this study indicate that capital structure and earnings management have a significant positive effect on firm value, while profitability and environment cost have a significant positive effect on firm value. Negative and significant, and free cash flow has a negative and insignificant effect on firm value.